Comparative profiling of bioactive compounds and antioxidant activity of extracts from selected medicinal plants: implications for mitigating obesity-related inflammation - Mngoma, Mlungisi F.; Magwaza, Lembe Samukelo; Mditshwa, Asanda; Tesfay, Samson Zeray; Mkhwanazi, Blessing N.; Nkomo, Mbukeni A. (Elsevier, 2025)
Obesity is a metabolic disorder, contributing to various health complications, including diabetes, hypertension, and cardiovascular dysfunction. Increased use of plant extracts to reduce obesity risk reflects consumer preference for natural remedies and scientific validation for their safety and efficacy. This study profiled bioactive compounds in methanolic extracts from the leaves and roots of Merwilla plumbea (Lindl.) Speta, Hypoxis hemerocallidea Fisch, Eucomis autumnalis (Mill.) Chitt, and Pentanisia prunelloides (Klotzsch) Walp. The objective was to explore and compare the medicinal properties of distinct plant parts for their potential to mitigate obesity-induced inflammation. P. prunelloides leaves and roots had higher concentrations of phenolics (123.92 mg/mL and 110.01 mg/mL) and flavonoids (44.4 mg/mL and 55.05 mg/mL), respectively. Gallotannins were significantly higher in H. hemerocallidea roots (5.19 mg/mL) while proanthocyanidins were predominantly found in P. prunelloides roots (35.77 mg/mL). The antioxidant activity was assessed by ferric reducing antioxidant potential (FRAP) and DPPH radical scavenging activity (RSA) assays. P. prunelloides roots had higher FRAP (2.97 mg/mL) and moderate DPPH (RSA) (52.89 %) while M. plumbea roots had the highest DPPH RSA (80.86 %) and lower FRAP (2.25 mg/mL). E. autumnalis roots and leaves showed FRAP values of 2.78 and 2.13 mg/mL, and DPPH RSA of 80.72 and 74.54 %, respectively. The results revealed that all plants investigated had considerable amounts of bioactive compounds with P. prunelloides showing the highest concentration, highlighting its potential for further pharmaceutical and nutraceutical exploration. Further research validating the bioactivity of key compounds in vivo, exploring seasonal variations, and assessing optimal harvesting practices is paramount for the sustainable utilization of these medicinal plants.
Keywords: Adipose; Antioxidants; Inflammation; Inhibition; Phytochemicals; 3108 Plant Biology; 31 Biological Sciences; 42 Health Sciences; 4208 Traditional, Complementary and Integrative Medicine; Obesity; Nutrition; Complementary and Integrative Health; Cardiovascular; 3 Good Health and Well Being; Plant Biology & Botany; 3108 Plant biology; 4208 Traditional, complementary and integrative medicine